h - Cavalca, Katia Lucchesi; Weber, Hans Ingo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
IFToMM conferences have a history of success due to the various advances achieved in the field of rotor dynamics over the past three decades. These meetings have since become a leading global event, bringing together specialists from industry and academia to promote the exchange of knowledge, ideas, and information on the latest developments in the dynamics of rotating machinery. The scope of the conference is broad, including e.g. active components and vibration control, balancing, bearings, condition monitoring, dynamic analysis and stability, wind turbines and generators, electromechanical interactions in rotor dynamics and turbochargers. The proceedings are divided into four volumes. This first volume covers the following main topics: Active Components and Vibration Control; Balancing; Bearings: Fluid Film Bearings, Magnetic Bearings, Rolling Bearings and Seals; and Blades, Bladed Systems and Impellers. .
Numerical Identification of Nonlinear Hydrodynamic Forces -- Thermo-Hydrodynamic Model Influence on First Order Coefficients in Turbocharger Thrust Bearings -- Study of Stiffness Reduced Order Model Applied to Line and Elliptical Contact Under EHD Lubrication -- Stiffness and Damping Reduced Model in EHD Line Contacts -- Dynamical Characteristic Analysis of Elastic Ring Squeeze Film Damper in Rotor System -- Unbalance Vibration Compensation Control Using Deep Network for Rotor System with Active Magnetic Bearings -- Unbalance Identification in a Rotor Supported by Active Magnetic Bearing -- Numerical study on the influence of Gas Foil Thrust Bearings on the vibrational behavior -- Magnetic Bearings for Non-static Flywheel Energy Storage Systems (FESS) -- The Application of Controllable Magnetorheological Squeeze Film Dampers for Minimizing Energy Losses and the Driving Moment of Rotating Machines.
Keywords: Machinery; Multibody systems; Vibration; Mechanics, Applied; Electric power production; Machinery and Machine Elements; Multibody Systems and Mechanical Vibrations; Electrical Power Engineering; Mechanical Power Engineering